Development of New Sustainable Pictorial Techniques: Aesthetic and Processual Contributions - Galbis Juan, Amparo (2024)
Introduction: From the Universitat Politècnica de València, thanks to the progress and perseverance in the research of alternative formulas, some paints favor eco-sustainability. Objective: This article analyzes the main advances and contributions made by this line of research, observing its performance in pictorial practice. Methods: Parallel to the study and formulation we have, it has been testing the usefulness and suitability of these binders in the creation of plastic work through various experimental tests. Results: Based on the generational ramification of the tempera pictorial technique, focused in a pioneering way on binding emulsions of semi-synthetic composition and handling of hydrophilic-lipophilic balance (BHL), its benefits and processual characteristics will be shown. Conclusions: The operational and creative possibilities of these emulsion tempers offer a renewal of plastic languages, expressive diversity, and procedural advantages. With the utmost commitment, an ethical and aesthetic performance of the materials, the quality of the processes is promoted, and the specificity of this knowledge is vindicated.